(untitled) (Journal of Management and Social Sciences, 2020)
This study investigated the personality variables of age, gender, experience, and subject background as determinants the cataloguing performance of librarians in Nigerian universities. A descriptive survey method was adopted in the study with the use of Cataloguers’ Personality Variables Questionnaire (CPVQ) and Cataloguers’ Practical Cataloguing Test (CPCT) designed by the researcher to collect data from 304 librarians in eighteen (18) university libraries from the six (6) geo-political zones of Nigeria. Descriptive statistic method was used to analyse data, answer research questions and test the hypotheses. The study revealed that each of the personal variables significantly influenced the cataloguing performance of librarians. The study, therefore, recommended, among other things, that library authorities should deploy librarians to the cataloguing section of the library based on the appropriate personal variables that are most suitable for achieving cataloguing efficiency among cataloguing librarians.